Effects of Motor Versus Cognitive Task Prioritization During Dual-Task Practice on Dual-Task Performance in Young Adults - Beurskens, Rainer; Brueckner, Dennis; Muehlbauer, Thomas (Frontiers in Psychology, 2020)
Background: Previous studies reported positive effects of concurrent motor and cognitive task practice compared to motor or cognitive task practice only on dual-task performance in young adults. Knowledge about the effect of motor versus cognitive task prioritization during practice on dual-task performance remains unclear and has not been investigated in depth so far. Thus, we examined the effects of motor compared to cognitive task prioritization during dual-task practice on motor-cognitive performance in healthy young adults. Methods: Healthy young adults were randomly assigned to dual-task (i.e., concurrent motor and cognitive practice; DT) or single-task (i.e., motor or cognitive task practice only; ST) practice groups. In DT practice, subjetcs were instructed to either prioritize the motor or the cognitive task during DT performance. The motor task required subjects to keep a stabilometer in a horizontal position. The cognitive task involved serial three subtractions. Outcome variables were the root-mean-square error (RMSE) for the motor task and the total number of correct calculations for the cognitive task. All participants practiced for two consecutive days under their respective treatment condition and were tested under DT condition 24 hours later (i.e., retention on day 3) without providing instructions on task prioritization. Results: Irrespective of prioritization (i.e., prioritize the motor task or the cognitive task), the DT practice groups similarly improved their DT motor and cognitive task performance. The ST groups also improved motor or cognitive performance depending on their respective training contents (i.e., motor practice improved RMSE and cognitive practice improved number of correct calculations but not vice versa). Conclusions: We conclude that DT compared to ST practice is well suited to improve DT balance performance, irrespective of task prioritization. DT but not ST practice resulted in an improved modulation of both domains (i.e., motor and cognitive) during DT performance. Our findings might be explained by freeing up central resources following DT practice that can be used to effectively perform the concurrent execution of motor and cognitive processing demands. However, this process is not further enhanced by the prioritized task domain.